Biomethics principles applied to epidemiological investigation - Olivero, Rosa; Domínguez, Antonio; Malpica, Carmen Cecilia (Acta Bioethica, 2008)
The need to regulate scientific activity has been increasing; it requires much more instruments for a strict bioethics checking. In 2002, the Council of the Medical Sciences’ International Organisations (CIOMS) updated the international patterns on biomedical and epidemiological ethics. This work examines the problems involved in this type of investigation.